The bubble and beyond : fictitious capital, debt deflation and the global crisis - Hudson, Michael (Dresden, 2012)
"THE BUBBLE AND BEYOND describes how the fabulous expansive forces of industrial capitalism have been subverted by a predatory finance capitalism. What the FED hailed as “The Great Moderation” has left the middle class to take on a lifetime of bank debt to obtain access to housing, education to get a job, an auto to drive to it, and simply to maintain living standards that wages and salaries no longer support. What has derailed the economy is the take-over of academic economics and politics by the financial sector in order to censor criticism and misrepresent statistics so as to give the impression that the economy can “borrow its way out of debt.” The reality is that income used to pay down today’s debt overhead is not available to be spent on goods and services. The result is debt deflation, followed by austerity and the the "fire sale" or decay of infrastructure at the national and local levels. The most controversial claim by Prof. Hudson is that “Debts that can’t be paid, won’t be.” The question he poses is whether their non-payment will lead to worldwide foreclosures – including sell-offs of the public domain by debt-strapped local and national governments – or whether they will be written down in line with the ability to pay. This is the economic issue that will dominate politics over the next generation. Illustrated with charts and exhibits that make it plain where money goes versus where it should go."